2019
DOI: 10.5194/soil-5-303-2019
|View full text |Cite
|
Sign up to set email alerts
|

Women's agricultural practices and their effects on soil nutrient content in the Nyalenda urban gardens of Kisumu, Kenya

Abstract: Abstract. In Kisumu up to 60 % of the inhabitants practice some form of urban agriculture, with just under 50 % of the workers being female. On average, women spend more hours a day in the gardens than men. Therefore women's knowledge is pivotal for effective agricultural management. To enhance and better use women's knowledge, gender-related sociocultural obstacles linked to land ownership, investment, and farm inputs have to be taken into account. We aimed to determine how the agricultural knowledge and moti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…This is because the urban agricultural sector tends to still use traditional marketing strategies so that it only settles down and does not experience development. Apart from that, one of the limitations of agricultural business in urban areas is the narrow size of the land so that in order to continue to grow urban agriculture must produce products as a continuation of its farming business not only limited to selling agricultural products but there Nurdiana / 7P Marketing Mix in Processed Farm Products by Urban Farming Businesses is development (Grebitus et al, 2020;Jonkman et al, 2019;Mhache & Lyamuya, 2019). This is what the Orchid Women Farmer Group is trying to implement.…”
Section: Discussionmentioning
confidence: 99%
“…This is because the urban agricultural sector tends to still use traditional marketing strategies so that it only settles down and does not experience development. Apart from that, one of the limitations of agricultural business in urban areas is the narrow size of the land so that in order to continue to grow urban agriculture must produce products as a continuation of its farming business not only limited to selling agricultural products but there Nurdiana / 7P Marketing Mix in Processed Farm Products by Urban Farming Businesses is development (Grebitus et al, 2020;Jonkman et al, 2019;Mhache & Lyamuya, 2019). This is what the Orchid Women Farmer Group is trying to implement.…”
Section: Discussionmentioning
confidence: 99%
“…At all sites, the soil is ploughed with hand tools to a depth of 30 to 50 cm. An earlier study [22] showed that very few of the urban farmers at the Kisumu sites use inorganic fertilizers, and techniques such as mulching and applying compost are preferred.…”
Section: Size Ownership and Crops At Ua Sitesmentioning
confidence: 99%
“…Two case studies were conducted. One was conducted in Kisumu, Kenya, where a previous pilot study indicated a link between current UA soil status and land use history [22], and one was conducted in Ouagadougou, Burkina Faso. An exploration was made of the social and historic contexts of three UA sites in each city, to better understand the reasons for the locations, size, and soil macronutrient content.…”
Section: Introductionmentioning
confidence: 99%
“…In Uganda, plant clinics were accessed differentially, with middle-aged male farmers attending more frequently than women (although overall male attendance was also low; Karubanga et al, 2017). In Kenya, although women spent more hours in the day in gardens, this did not translate into better soil nutrient quality (Jonkman et al, 2019). Organic agriculture in the Kenyan counties of Kajiado and Murang'a was more likely where there was higher gender equity (Kamau et al, 2018).…”
Section: Erential Agricultural Practices and Outcomesmentioning
confidence: 99%